Tribal women : yesterday, today, and tomorrow - "Tribal Women: Status, Challenges, and Possibilities" (Seminar) (2013 : Bhopal, India); Chaudhary, S. N. (Shyam Nandan), 1954-; Tribal Research and Development Institute (Jaipur Rawat Publications, 2017)
Papers presented at the two days National Seminar entitled "Tribal Women: Status, Challenges, and Possibilities" organized by Tribal Research and Development Institute, Bhopal in March 2013.
Includes bibliographical references and index.
Keywords: Rural women -- India -- Social conditions -- Congresses; Women in development -- Government policy -- India -- Congresses; Indigenous women -- India -- Social conditions -- Congresses; Tribes -- India -- Congresses